Desenvolvimento de técnicas de produção de Codium tomentosum em substratos artificiais - Mata, João Ricardo de Almeida (2021)
ds, due to their chemical composition, which exhibit multiple bioactive health effects and high potential to be used in many industries. Codium tomentosum is a green and perennial macroalgae, which can reproduce itself by sexual and asexual reproduction. This alga reveals high potential to be used in cosmetics and directly on human’s diet due to its nutritional composition and content in bioactive compounds. Inserted in an IMTA (Integrated Multitrophic Aquaculture) system, the aim of this work consists on the evaluation of the cultivation potential of Codium tomentosum attached to different types of substratum, colonization methods and different mediums. Five trials were made in order to determine key aspects of Codium tomentosum cultivation attached to the substrates, to evaluate and optimize the cultivation of C. tomentosum fixed on artificial substrates, in contrast to the freefloating method currently used at ALGAplus. In the first two trials, the substrates were submitted to colonization methods with a certain density. In the last three trials, the substrates were also submitted to both colonization methods with different density, kept in the maternity with controlled conditions and then transferred to the exterior, to an earth pond or to an artificial tank. In the first and second trials, the substrates tested were rope, plastic web, brick, rough rock, and tile using a passive seeding method with low density. However, it was not possible to cultivate Codium attached to them. After those results, the substrates used were changed to substrates already tested to cultivate other algae species attached to them, kuralon line. In this third trial, this was the substrate tested using a passive seeding method with medium density. Again, it was not possible to cultivate Codium. After this result, the density was increased to high values and another method of seeding, aspersion, was tested along the passive seeding method on kuralon line and biodegradable stripes. In the fourth trial, the Codium started to grow but when were transferred to the outside tanks got contaminated by other algae. With these results, another trial was performed using kuralon line where the density was maintained and in the second step of the cultivation the substrates were transferred to an artificial tank. In this trial, the cultivation of Codium attached to the substrates was achieved when subjected to the aspersion method. According to the results of the five trials made, the substrate used with the best results was the kuralon line, the best density was high and the best colonization method was the aspersion method.